Outcomes of laparoscopic abdominal cerclage in Aevitas Fertility Clinic in South Africa from 2018-2022 : a retrospective study - Mbungu, Nomaphelo (Stellenbosch : Stellenbosch University, 2024)
Thesis (MMed) -- Stellenbosch University, 2024.